Metabolomic Profiling Identifies Novel Circulating Biomarkers of Mitochondrial Dysfunction Differentially Elevated in Heart Failure With Preserved Versus Reduced Ejection Fraction: Evidence for Shared Metabolic Impairments in Clinical Heart Failure. Issue 8 (August 2016) - Hunter, Wynn G.; Kelly, Jacob P.; McGarrah, Robert W.; Khouri, Michel G.; Craig, Damian; Haynes, Carol; Ilkayeva, Olga; Stevens, Robert D.; Bain, James R.; Muehlbauer, Michael J.; Newgard, Christopher B.; Felker, G. Michael; et al.
Abstract : Background: Metabolic impairment is an important contributor to heart failure (HF) pathogenesis and progression. Dysregulated metabolic pathways remain poorly characterized in patients with HF and preserved ejection fraction (HFpEF). We sought to determine metabolic abnormalities in HFpEF and identify pathways differentially altered in HFpEF versus HF with reduced ejection fraction (HFrEF). Methods and Results: We identified HFpEF cases, HFrEF controls, and no‐HF controls from the CATHGEN study of sequential patients undergoing cardiac catheterization. HFpEF cases (N=282) were defined by left ventricular ejection fraction (LVEF) ≥45%, diastolic dysfunction grade ≥1, and history of HF; HFrEF controls (N=279) were defined similarly, except for having LVEF <45%. No‐HF controls (N=191) had LVEF ≥45%, normal diastolic function, and no HF diagnosis. Targeted mass spectrometry and enzymatic assays were used to quantify 63 metabolites in fasting plasma. Principal components analysis reduced the 63 metabolites to uncorrelated factors, which were compared across groups using ANCOVA. In basic and fully adjusted models, long‐chain acylcarnitine factor levels differed significantly across groups ( P< 0.0001) and were greater in HFrEF than HFpEF ( P =0.0004), both of which were greater than no‐HF controls. We confirmed these findings in sensitivity analyses using stricter inclusion criteria, alternative LVEF thresholds, and adjustment for insulin resistance. Conclusions: We identified novel circulating metabolites reflecting impaired or dysregulated fatty acid oxidation that are independently associated with HF and differentially elevated in HFpEF and HFrEF. These results elucidate a specific metabolic pathway in HF and suggest a shared metabolic mechanism in HF along the LVEF spectrum.